2017
DOI: 10.1016/j.marpolbul.2017.06.024
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nutrient pollution on dinoflagellate cyst assemblages across estuaries of the NW Atlantic

Abstract: We analyzed surface sediments from 23 northeast USA estuaries, from Maine to Delaware, and nine estuaries from Prince Edward Island (PEI, Canada), to determine how dinoflagellate cyst assemblages varied with nutrient loading. Overall the abundance of cysts of heterotrophic dinoflagellates correlates with modeled nitrogen loading, but there were also regional signals. On PEI cysts of Gymnodinium microreticulatum characterized estuaries with high nitrogen loading while the sediments of eutrophic Boston Harbor we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 64 publications
1
19
0
Order By: Relevance
“…Indeed, the different responses according to the studied estuaries can be explained by the different physico-chemical configurations (e.g. salinity, pH) (Price et al 2017). Our results appear similar to those obtained by Pospelova et al (2002), who concluded that L. machaerophorum does not respond positively to human inputs in shallow estuaries, having fewer consequences on water mass stratification than in deep Norwegian fjords (Dale et al, 1999;Dale, 2009).…”
Section: Accepted Manuscript 24supporting
confidence: 85%
“…Indeed, the different responses according to the studied estuaries can be explained by the different physico-chemical configurations (e.g. salinity, pH) (Price et al 2017). Our results appear similar to those obtained by Pospelova et al (2002), who concluded that L. machaerophorum does not respond positively to human inputs in shallow estuaries, having fewer consequences on water mass stratification than in deep Norwegian fjords (Dale et al, 1999;Dale, 2009).…”
Section: Accepted Manuscript 24supporting
confidence: 85%
“…biodiversity changes, invasive species). Due to increasing urbanization and agriculture growth, nutrient pollution has become a major concern in many coastal regions (e.g., Carpenter et al, 1998;Rabalais, 2002;Price et al, 2017b). For example, over 65% of US estuaries are considered as moderately to highly eutrophicated (Bricker et al, 2008).…”
Section: Dinocyst-based Paleoecological Reconstructions On Coastal Eumentioning
confidence: 99%
“…However, regarding the whole dinoflagellate community, there is no consensus on a fossil dinocyst assemblage-type that would reflect nutrient enrichment in disturbed estuarine environments (Pospelova et al, 2002). Price et al (2017b) concluded that there is no single species that characterizes eutrophic estuaries or high nutrient loading. Large fluctuations in cyst production are then frequently observed and amplified by the abrupt increase of one or two regionally specific taxa (for example Spiniferites spp.…”
Section: Dinocyst-based Paleoecological Reconstructions On Coastal Eumentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, assemblage composition, abundance, and morphology can reflect the conditions prevailing at the time of cyst formation (Ellegaard et al, 2002;Godhe and McQuoid, 2003;Price and Pospelova, 2011;Heikkilä et al, 2016). The coupling between modern dinoflagellate cyst assemblages and corresponding environmental conditions (Godhe and McQuoid, 2003;Price et al, 2017) can be used to infer past environmental conditions. For example, dinoflagellate cyst records have been used to investigate past changes in sea surface conditions, such as temperature (e.g., Brinkhuis et al, 1998, de Vernal, et al 2001, Bringué et al, 2018, salinity (e.g., Wall & Dale, 1973;Head et al, 2004;Sorrel et al, 2006), sea-ice cover (e.g., Durantou et al, 2012), as well as changes in regional climate variability vs. anthropogenic change (e.g., Ribeiro et al, 2016) and in water quality due to eutrophication (e.g.…”
Section: Introductionmentioning
confidence: 99%